Granulomas due to echinoids – sea urchin – (...When the patient knows more than the doctor). - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
At the end of July a 20-year-old boy came to the clinic. As usually I took up the history talking about moderately symptomatic lesions of the dorsal aspect of the hands and extensor surface of the knees from three months. There was no personal or family history of atopy. After collecting the history (without understanding anything) I watched the skin lesions (Fig. 1, 2); after a moment of confusion, I said to myself aloud: this is an occupational disease. I asked him: «What is your job?». «Diver» he responded. «What exactly?». «I pick up what I find on the sea bed and sell it». «Even sea urchins?». «Of course, I pick up one hundred and half kilos a day and sell them at 1 euro per kilo, but only from May to September». «We found the cause». «I knew it, but the dermatologist told me that I was affected by an atypical mycobacterial infection and gave me oral corticosteroids and antibiotics (and he showed me the prescription) that did not improve my problem». Intrigued, I said: «And in the other months what do you pick up from the sea bed?». «Sea cucumbers (i.e. Holothurian, commonly called sea cucumbers) and I sell them to the Chinese people at 3 Euro per kilo». «Why did you not just tell me that the sea urchins were responsible?». «I wanted to see if you understood it by yourself».